Health in the new millennium - Nevid, Jeffrey S. (Worth Publishers, 1998)
How can we prepare ourselves and our students for the health challenges that await us. This book can help to find the answers.... This book is written ... to provide students with the skills they need to meet challenges to their health and optimize their physical and psychological well-being. [The book] offers the necessary breadth and currency of coverage. [The authors] examine topics including fitness, nutrition, mental health, and infectious and chronic diseases in a way that distills the most important information and makes it accessible and interesting to readers. -Pref.